The Way to Socialism? First Five-Year Plan for the Development of Bulgarian Agriculture - Penchev, Pencho (Research Papers, 2018)
The author of the study aims to answer the question whether before September 1944 in Bulgaria there were tendencies and political practices that lead to the establishment of socialist economic and social model. For this purpose, an analysis of the 1941 Five-year agricultural plan has been made. The main conclusion on the basis of the Five-year plan is that the establishment of a socialist economic model in Bulgaria was by no means a surprise, and that the basic characteristics of this model were supported even by people who are not political socialists. The Five-year plan is an illustration of the gravitational forces towards socialism in Bulgarian society, which has the potential to accelerate this movement through its policies.